2020
DOI: 10.22541/au.158981188.83217663
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The association of new-onset atrial fibrillation and risk of cancer: A systematic review and meta-analysis

Abstract: Background There are distinct results for the relationship between new-onset atrial fibrillation (NOAF) and subsequent incident cancer. To date, no systematic analysis has been conducted on this issue. This study aims to explore the relationship between NOAF and the risk of developing cancer through a meta-analysis with a large sample size. Methods Electronic databases, such as PubMed and EMBASE, were searched for published relevant studies on NOAF patients diagnosed with cancer after and during follow-ups, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…A previous study observed that AF is not uncommon in hospitalized patients with lung cancer, and AF significantly prolonged hospital stay and care cost, suggesting potential adverse effect of AF on lung cancer (12). Moreover, another meta-analysis found a close association between diagnosis of NOAF within 90 days and risk of lung cancer, further extend the association between AF and lung cancer, and suggested the importance of detecting AF in patients with lung cancer (13).…”
Section: Discussionmentioning
confidence: 82%
“…A previous study observed that AF is not uncommon in hospitalized patients with lung cancer, and AF significantly prolonged hospital stay and care cost, suggesting potential adverse effect of AF on lung cancer (12). Moreover, another meta-analysis found a close association between diagnosis of NOAF within 90 days and risk of lung cancer, further extend the association between AF and lung cancer, and suggested the importance of detecting AF in patients with lung cancer (13).…”
Section: Discussionmentioning
confidence: 82%
“…Our research is somewhat pioneering. Two previous metaanalyses reported an increased risk of cancer diagnosis within 90 days in patients with newly developed atrial fibrillation, but these studies focused on all malignancies rather than specific tumor subtypes (71,72). A recent meta-analysis reported the prevalence of atrial fibrillation in breast cancer patients across different types of cancer therapy (73).…”
Section: Comparison With Previous Studiesmentioning
confidence: 99%